2006
DOI: 10.1002/mop.22024
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an E‐shaped patch antenna

Abstract: This paper presents the theoretical and simulation investigations of an E‐shaped patch antenna applicable in modern mobile communications. It shows marked improvement in the bandwidth when compared with rectangular patch antenna with acceptable radiation pattern. Further, the bandwidth is optimized with respect to notch length, width, and position. Typically, the antenna shows an enhanced impedance bandwidth of 32.5%. © 2006 Wiley Periodicals, Inc. Microwave Opt Technol Lett 49: 4–7, 2007; Published online in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…4 can be calculated from (18) In (18), is the input impedance of patch equivalent and is the input impedance of feed strip. …”
Section: Complete Equivalent Circuitmentioning
confidence: 99%
See 2 more Smart Citations
“…4 can be calculated from (18) In (18), is the input impedance of patch equivalent and is the input impedance of feed strip. …”
Section: Complete Equivalent Circuitmentioning
confidence: 99%
“…Extensive studies have been reported in the literature on input impedance calculations of microstrip antennas [11]- [22]. A few of these studies include transmission line model [11], cavity model [12], moment method solutions [13]- [17], equivalent circuit (extracted from cavity model i.e., treating volume below the patch as a cavity) approaches [18]- [21], some of which involve solving complicated integrals. An equivalent circuit based approach provides a clear physical insight into the operation of the antenna.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig.3 (b) the E-shaped patch has three arms which affect the current distribution on the surface of the patch. In the center arm the current flows normally and represents the ordinary RLC equivalent circuit but for the two side arms the current has to bend around the slot and this creates longer current path as illustrated in Fig 1. This increment of current path results an additional series inductance (∆L p ) [4].The slot also contributes to additional series capacitance (∆C p ) as shown in Fig 3(a).Therefore, the equivalent circuit model of the E-shaped patch unit cell has two resonators which are connected by a coupling capacitor (C c ). As the proposed flat lens antenna unit cell consists of two back-to-back E-shaped patches, the equivalent circuit model of the unit cell is also comprises of two identical circuits linked by a coupling transformer as sketched in The equivalent circuit parameters are analytically determined as follows: The value of L p and C p can be defined as [4,8].…”
Section: Electrical Modeling Of the Unit Cellmentioning
confidence: 99%
“…This is to obtain the physical insight of the structure and to analytically determine the lumped element parameters while considering the element's physical characteristics. In the related literature, an equivalent electrical model of several rectangular patch antennas loaded by different slot configurations are proposed [3][4][5]. An equivalent circuit model of discrete lens antenna unit cell patches connected by metalized via is also presented [6].…”
Section: Introductionmentioning
confidence: 99%